Perkembangan dan Peranan Multimedia (Internet) Berbasis Dakwah Islam - Erwan Efendi; Natasya Piliang; Yanzah Zahir (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
The spread of information and communication technology media is intended to facilitate the needs of modern society, especially religious knowledge. Networked communication media is increasingly spreading to almost all circles. Social media networks are increasingly spreading to almost all circles. Networked social media apart from being a means of communication and information, is also a benchmark for today's society's culture. The notion that "today's society is 'obsessed' with technological sophistication", so that people experience a dilemma in life, which tends to exist in the media or leave it. The fact that the use of social media reduces physical interaction even tends to social antipathy. Therefore, the obligation of da'wah must be synergized dynamically; da'wah through the internet with cultural propaganda. That the effectiveness of da'wah for the technological community is the harmony of cultural da'wah with the conditions of virtual society, especially the industrial generation. Keywords: Cultural Da'wah, Virtual Da'wah, Internet, Maya Society.